Honoring Indigenous culture-as-intervention: Development and validity of the Native Wellness AssessmentTM. Issue 2 (3rd April 2017) - Fiedeldey-Van Dijk, Carina; Rowan, Margo; Dell, Colleen; Mushquash, Chris; Hopkins, Carol; Fornssler, Barb; Hall, Laura; Mykota, David; Farag, Marwa; Shea, Bev
ABSTRACT: There is a need for Indigenous-centered research to appraise culture's role in wellness. Researchers described the development and validity of the Native Wellness Assessment (NWA TM ). The NWA has culture-as-intervention at its apex. Wellness, culture, and cultural intervention practices (CIPs) are explored from an Indigenous perspective. Indigenous clients completed matching self-report and observer versions of the NWA at three time points during addictions treatment. Statistically and psychometrically, the NWA content and structure performed well, demonstrating that culture is an effective and fair intervention for Indigenous peoples with addictions. The NWA can inform Indigenous health and community-based programs and policy.